Can Attention Deficits Predict a Genotype? Isolate Attention Difficulties in a Boy with Klinefelter Syndrome Effectively Treated with Methylphenidate - Antonella Gagliano; Eva Germanò; Loredana Benedetto; Gabriele Masi (Hindawi Limited, 2014)
This paper describes a 17-year-old boy who was diagnosed with Klinefelter syndrome (KS) (XXY) at the age of 16 years. Although cognitive level was absolutely normal, he showed attentional difficulties that negatively affected school adjustment. He was successfully treated with methylphenidate. A significant improvement was observed in the ADHD Rating Scale IV and in the inattention subscale score of the Conners Scales. The CGI-S score improved from 3 to 1, and the CGI-I score at the end point was 1 (very much improved). Also attention measures, particularly forward and backward digit span, improved with MPH treatment. Given the widely variable and often aspecific features, KS may run undiagnosed in a large majority of affected patients. A close attention to the cognitive phenotype may favour a correct diagnosis, and a timely treatment.